Pengaruh Profitabilitas Dan Struktur Modal Terhadap Nilai Perusahaan Manufaktur Terdaftar Di Bursa Efek Indonesia - Dian Indah Sari; Slamet Marsoyo (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2022)
Abstract This study aims to determine the effect of profitability and capital structure on firm value. This research is a quantitative descriptive research. This study obtained data through library studies sourced from literature studies, books, journals related to the research title. This research was obtained from data on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. Data analysis techniques in this study with multiple linear regression analysis include the T test, F test and the coefficient of determination test. The conclusions obtained based on the results of the above discussion include (1) Profitability partially has a positive and significant influence on firm value. (2) Capital structure partially positive and significant effect on firm value. (3) Profitability and capital structure simultaneously have a significant and positive effect on firm value. Keywords: Profitability, Capital Structure, Firm Value